Factors associated with adolescent pregnancy: a systematic scoping review - Soto Flores, María (2023)
Objective: to describe the factors associated with adolescent pregnancy, both risk and protective. Methodology: the present systematic review was built based on the guidelines (PRISMA ScR) and manuals (JBI), once the databases were selected, the advanced search equation was entered with the DeCS / free terms and the Boolean operators; Once the appropriate studies were selected, we moved on to the screening phase by applying readability methods. Conclusion: it is concluded that the risk factors, such as: low educational level, deteriorated emotional state, family dysfunction, medium-low economic level, living in rural areas, and difficult access to health services, On the other hand, The protective factors are: high level of knowledge about family planning methods, as well as a high level of education; And at an interpersonal level, protection is provided by having a stable romantic partner and having good family relationships, which positively influence the prevention of this problem.